1965
DOI: 10.1001/archpedi.1965.02090020123005
|View full text |Cite
|
Sign up to set email alerts
|

Breast Nodule in Premature Infant

Abstract: LITTLE REFERENCE has been made to the size of the breast of the newborn except that hyperplasia, engorgement, and milk secretion is physiologic, and that hyperplasia is seen with equal frequency in mature infants of both sexes. It also has been stated that breast development is rarely seen in premature infants, but a detailed study of the latter point has not been presented.* 1 In this study, the relationship between the size of the breast nodule and the birth weight and gestation was examined. The data are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1966
1966
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This finding was not associated with differences in body weight or amount of subcutaneous fat tissue. Most previous studies have shown no gender difference in the occurrence or size of breast tissue in newborn infants (2)(3)(4)11). At later ages, from 1-2 mo up to 1 y, some have reported palpable breast tissue to be more frequent in girls than in boys (4,6) whereas other studies could not reproduce a gender difference (2,3).…”
Section: Discussionmentioning
confidence: 97%
“…This finding was not associated with differences in body weight or amount of subcutaneous fat tissue. Most previous studies have shown no gender difference in the occurrence or size of breast tissue in newborn infants (2)(3)(4)11). At later ages, from 1-2 mo up to 1 y, some have reported palpable breast tissue to be more frequent in girls than in boys (4,6) whereas other studies could not reproduce a gender difference (2,3).…”
Section: Discussionmentioning
confidence: 97%